Corrosion and wear mechanisms of rare earth (Gd, Sc, Y)-doped Zr-based amorphous alloys - Zulai Li; Wengao Zhang; Mulan Peng; Wei He (Journal of Materials Research and Technology)
Rare-earth elements have been utilized in the design and development of new amorphous alloys to improve the corrosion and wear resistance of Zr-based amorphous alloys. In this study, a rare-earth doped Zr-based amorphous alloy (Zr-BMG(RE)) was prepared by the copper mold casting method, which was investigated by corrosion and wear experiments. The results show that Zr-BMG(RE) has a completely amorphous structure, and the doping of rare earths Gd and Y raises the crystallization transition temperature of the amorphous. The addition of rare earth elements Gd and Sc increases the microhardness of Zr-based amorphous alloys, while rare earth element Y causes a slight decrease in microhardness. Gd and Sc will make Zr-based amorphous materials corrosion current density increases, the material pitting and localized corrosion, acid corrosion resistance is reduced. Y doping improves the self-corrosion potential of Zr-based amorphous alloys, reduces the corrosion current density, the surface passivation film is the densest, and the degree of charge transfer on the metal surface is the most difficult, Zr-BMG(Y) has a better corrosion resistance compared with other alloy materials. Zr-BMG(Gd) has the smallest friction rate (1.72 × 10−7mm3N−1mm−1), and the wear rates of the rare earth doped Zr-based amorphous alloys are all smaller than that of Zr-BMG, and the main loss mechanism of Zr-based amorphous alloys is the interaction of adhesive wear, abrasive wear, oxidative wear and fatigue wear. The mechanism of corrosion and wear resistance of rare earth to Zr-based amorphous alloys is discussed, which provides a new idea for the design of amorphous alloys.